Distribution of Deep-Sea Sponge Aggregations in an Area of Multisectoral Activities and Changing Oceanic Conditions - Kazanidis, Georgios; Vad, Johanne; Henry, Lea-Anne; Neat, Francis; Berx, Barbara; Georgoulas, Konstantinos; Roberts, J Murray (Frontiers in Marine Science, 2019)
Discovery and understanding of fragile deep-sea habitats like sponge aggregations, are being outpaced by anthropogenic resource exploitation. Sustainable ocean development in the Faroe-Shetland Channel Nature Conservation Marine Protected Area (FSC NCMPA; northeast Atlantic), which harbours sponge aggregations, now requires adaptive management in the face of encroachment of multisectorial activities in this area (e.g. fishing, oil and gas, shipping) and climate change. We examined sponge morphotype composition, richness, diversity, density and body-size distribution inside and outside the FSC NCMPA, and the role of environmental variability and human impact in these sponge aggregations. Analyses were based on the examination of 465 high resolution images from 13 towed-camera transects. A catalogue for regional sponge morphotypes was also developed and applied for these analyses. Analysis revealed that morphotype composition did not differ between inside and outside the FSC NCMPA but richness, diversity and densities of massive/spherical/papillate and flabellate/caliculate sponges were higher inside than outside the boundary. The sponge aggregations occurred within a narrow zone between 450 and 530 m depth, within relatively warm and saline water masses. Furthermore, multiple size cohorts of sponges were recorded inside the FSC NCMPA, in contrast to the single cohort outside. Distance-based linear modelling showed that demersal fisheries, substratum, salinity and temperature explained a statistically-significant amount of variation (48%, p<0.001) of sponge density across the study area. Findings on density and size cohorts suggest that the FSC NCMPA boundary currently encloses the most vulnerable area, which also demonstrates normal ecosystem functions (e.g. recruitment). However, sponges were constrained to a narrow environmental niche shaped by fisheries and interactions of FSC NCMPA water masses with the slope that in turn likely determine, food supply to the sponge aggregations. Our study illustrated the vulnerability of the FSC NCMPA sponge aggregations to fisheries and changes to water mass properties over time. The morphotype catalogue and suite of indicators (i.e. density and body-size distribution) allow for baseline and future assessments of anthropogenic and climate change impacts on sponge aggregations’ environmental status in the FSC NCMPA, thus guiding management as sectoral encroachment continues in this area.